The impact of anterior knee displacement on knee joint load during the forward bow step in Tai Chi - Hua, Lijun; Bi, Gengchao; Zhang, Yanlong; Wang, Kai; Liu, Jiao (Frontiers in Bioengineering and Biotechnology, 2024)
Background: While the forward bow step is a crucial component of Tai Chi (TC) practice, little research has been conducted on its impact on knee joint load and muscle coordination. This study aims to investigate the effects of three different knee forward positions during the TC forward bow step on knee joint loading. Method: Twenty TC practitioners were recruited, and motion capture systems, force platforms, and surface electromyography were utilized to synchronously collect biomechanical parameters of three types of forward bow steps: knee joint not exceeding the tip of the foot (NETT), knee joint forward movement level with the tip of the foot (LTT), and knee joint forward movement exceeding the tip of the foot (ETT). Ligament and muscle forces were calculated using OpenSim software for musculoskeletal modeling and simulation. One-way ANOVA was used to analyze the variations of the indicators during the peak anterior displacement of the knee joint in three movements. Additionally, spm1d one-way ANOVA was employed to examine the variations in the one-dimensional curve of the indicators throughout the entire movement process. Results: Compared with LTT and ETT, the NETT posture was associated with significantly decreased knee flexion angle (F=27.445, p=0.001), knee anterior-posterior translation (F=36.07, p<0.001), flexion-extension torque (F=22.232, p=0.001), ligament force (F=9.055, p=0.011). Additionally, there was also a significant reduction in muscle strength, including quadriceps (F=62.9, p<0.001), long biceps femoris (F=18.631, p=0.002), lateral gastrocnemius (F=24.933, p=0.001) and soleus (F=7.637, p=0.017). Conclusion: This study further confirms that in the forward lunge movement of Tai Chi, the knee joint load is mainly concentrated during the forward movement phase. Compared to the knee joint load at the NETT position, the load is greater at the LTT position; and compared to the LTT position, the load is even greater at the ETT position.